Arabic language learning based on the Merdeka Curriculum: Problems and Solutions - Ahmad Imam Baihaqi; Hanik Mahliatussikah; Nur Hidayati; Moh Khasairi (Fakultas Tarbiyah Program Studi Pendidikan Bahasa Arab Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2025)
Changing the curriculum requires various academic communities to quickly adapt to all changes. The Merdeka Curriculum at MAN Kota Blitar was only implemented in the 2023/2024 school year. This study aims to describe the problems of teachers and students in learning Arabic using the Merdeka Curriculum at MAN Kota Blitar. Researchers used case study research with data collection techniques in the form of observation, questionnaires, interviews, and documentation. The collected data were analyzed by following the stages of Miles & Huberman, namely reduction, presentation, and conclusion drawing. The results of the study found that the problems faced by teachers focused on the pedagogical aspects of teaching, namely (1) developing teaching modules for the Merdeka Curriculum, (2) choosing a learning model that is relevant to the Merdeka Curriculum, and (3) applying formative assessment in learning. Meanwhile, student problems are classified into internal and external problems. Internal problems faced by students in learning Arabic are (1) lack of basic Arabic language skills and (2) low motivation to learn. While external problems are (1) a less supportive environment and (2) limited learning resources.